Monitoring of common adulterants in raw milk in different agroclimatic zones of Rajasthan - Sharma, Sanjita; SHARMA, vishnu; Mathur, Manisha; Singh, Navav; Pandey, Anurag (Indian Journal of Animal Production and Management, 2018)
Present study was carried out to monitor the present status of quality of raw milk sold in different agroclimaticzones of Rajasthan. Total 1650 raw milk samples were randomly collected from animal farm,milk vendors and sweet shops (Halwai) from different agro-climatic zones of Rajasthan and carried outinvestigations to detect the presence of various adulterants. The results of present study revealed thatthe percent adulteration of different adulterants in milk are urea 6% ( n=99), soda 8% ( n=132), salt 2.54%(n=42), starch 1.93% (n=32), detergent 8.12% (n=132) and added water 53.21% (878). The study indicatesthat there is trend of adulteration of raw milk sold in different parts of Rajasthan affecting the nutritive valueof milk and may also cause human health problems.